2015
DOI: 10.1016/j.chb.2015.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ experiences and perceptions of digital technology: (Dis)empowerment, wellbeing, and inclusion

Abstract: As more and more of the business of society is transferred and conducted online, older adults frequently find themselves without the skills to participate effectively. This is frequently confounded by limited physical mobility and a decrease in their social network and contact. This paper examines the lived reality of that process and how digital technology could be used to enhance the life activity of older adults and their wellbeing by increasing their social network. Seventeen older adults (10 female, 7 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
226
0
61

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(304 citation statements)
references
References 57 publications
17
226
0
61
Order By: Relevance
“…older adults with a lower education level are less likely to use different technologies [10] [50]. On the other hand, it has been suggested that digital technology can protect older adults from the digital divide [22].…”
Section: Mobile Technology Supporting Wellness In the Young Elderlymentioning
confidence: 99%
“…older adults with a lower education level are less likely to use different technologies [10] [50]. On the other hand, it has been suggested that digital technology can protect older adults from the digital divide [22].…”
Section: Mobile Technology Supporting Wellness In the Young Elderlymentioning
confidence: 99%
“…These attitudes focus on the perceived usability and usefulness of social technology to reexamine the perception that older adults are not motivated to learn new technologies or find them too difficult to use. 4 …”
Section: 28mentioning
confidence: 99%
“…[3][4][5] This research paints a bleak picture of older adults-that they lack the ability and motivation to adapt to a changing technological landscape. Many older adults feel anxious and intimidated by the thought of using new technologies or their security.…”
Section: Older Adults and Social Technology Usementioning
confidence: 99%
“…This is particularly true for chronic pain that is often highly variable. (34) They also indicated that a simple interface, technical support, and clear instructions are needed to tackle the technological barriers, consistent with other studies (29,35). App interface customization was also a recurring theme across the focus group discussions, to tailor the app to individual needs and preferences of the users, and to accommodate hearing and visual impairment, further underlining the need for usability and accessibility.…”
Section: Discussionmentioning
confidence: 50%